The Blood Lead Level of Subjects Exposed to Lead’s Polluted Air in Denpasar - Adiputra, Nyoman; HIS, Suyasning (Bumi Lestari; Vol 5 No 2, 2012)
Denpasar as a multi-center of human activities, many workers are go in to find ajob. The high mobility of human being associated by the transportation system which usethe leaded-petrol. Therefore, it is reasonably produces an air pollution, such particulatematter and lead. A cross-sectional study was conducted in Denpasar with the aim was tocheck the blood lead of subject of group of people. Blood lead was measured using theGraphite-Furnace technique and for the haemoglobin using spectrophotometer.Questionnaires also provided to know whether the subject are complaining anysubjective feeling of lead intoxication. Results found are: there was a significantdifference of blood level lead on subjects measured. The same thing also found on thehaemoglobine level. In tracing the trend of effluent’s cause, the secondary data on thelevel of air concentration lead in the consequtive three year. Data for gasoline sold outdaily in Denpasar Municipality also taken into consideration. The conclusion could be2drawn are: 1) the level of lead pollutant in Denpasar Municipality had been aboved thethgreshold level; 2) an increased blood lead level in subjects, as an indicator of inhaledair had been polluted by lead; 3) it is suspected that signs perceived by the subject,resulted from a polluted air due to lead.
Keywords: pollutant, lead, blood lead level.